Changes in the level of motor skills of young players as an indicator of the effectiveness of training for the football club "Gedania" Gdańsk - Stankiewicz, Błażej Stanisław; Łukasiak, Marcin; Pabianek, Łukasz (Journal of Education, Health and Sport, 2016)
The main objective of the study was to assess the quality of training of the football club "Gedania 1922" Gdańsk. This object is achieved by analyzing the theoretical information regarding football as a sport, club activities examined and the analysis of periodic fitness tests conducted four times from January 2015 to January 2016 on a group of forty boys aged 10-11 years attending football training in "Gedania" club. In order to know the level of efficiency of the overall respondents made attempts involving the running for 5, 15 and 30 meters, the long jump with space and running zigzag "on the envelope" without the ball. In turn, the efficiency of the special subject assessment using: running zigzag "on the envelope" with the ball, the ball hits the bench with a distance of 3 meters in 30 seconds and juggling. The study revealed that in terms of the whole period considered for all classes that make up the physical test has been to improve the average results obtained by the test participants, the particularly preferred changes were found in regards specific fitness. The study revealed that in terms of the whole period considered for all classes that make up the physical test has been to improve the average results obtained by the test participants, the particularly preferred changes were found in regards specific fitness. The test results also allowed efficiency to notice certain problem areas or requiring improvement. Nevertheless, the overall results of the research allowed to draw final conclusions about the quality of football training the children in the club Gedania Gdańsk.